Metaverse Learning in Educational Technology: Transforming the Learning Environment in the Era of Virtual Education - Samsidar Samsidar (EduTech Journal, 2026)
The rapid development of digital technology has opened new opportunities to transform learning spaces through metaverse-based approaches. This study examines the concept of Metaverse Learning within the framework of Educational Technology, focusing on how immersive virtual environments can redesign the learning experience in the virtual education era. Using a systematic literature review methodology, this study analyzed 20 primary references published between 2022 and 2026, identifying key trends, challenges, and opportunities in the implementation of metaverse learning. The results show that metaverse learning environments demonstrate significant advantages over traditional learning in terms of student engagement (87% vs. 62%), knowledge retention (82% vs. 65%), and collaborative learning capacity (91% vs. 54%). Furthermore, the integration of artificial intelligence, augmented reality, and virtual reality within the Edu-Metaverse ecosystem creates a more personalized and inclusive learning experience. However, challenges such as technological infrastructure, digital equity, data privacy, and the need for educator training remain critical barriers. This study concludes that metaverse learning represents a transformative paradigm shift in educational technology, and its successful implementation requires a comprehensive, multi-stakeholder approach involving educators, technology developers, policymakers, and students. Implications for educational technology practice and future research directions are discussed.